Semi‐Natural Habitats Buffer the Effects of Crop Diversification on Arthropod Pest Control Services in Agricultural Landscapes - Thomas Perrot; Léa Beaumelle; Eva Thomine; Yann Tricault; Nicolas Desneux; Matthias Albrecht; Péter Batáry; Felix Bianchi; Klaus Birkhofer; Aliette Bosem Baillod; Rebecca Chaplin‐Kramer; Anne‐Marie Cortesero; et al. (Ecology Letters, 2026)
Crop diversification is a promising strategy to strengthen pest control services in agricultural landscapes. Diversifying crops may limit pests through host crop dilution or by enhancing top‐down control by their enemies. However, crop diversification may also benefit generalist pests through higher resource continuity. Using a large‐scale dataset encompassing 742 landscapes across 13 countries, we assessed the impact of landscape‐scale crop diversity on the abundance of natural enemies, the potential for biological control, and insect pest abundance. Crop diversification did not increase the overall abundance of natural enemies or the potential for biological pest control. Instead, crop diversity primarily favoured the abundance of specialist natural enemies and pests in highly simplified landscapes, an effect that was reduced in landscapes with high proportions of semi‐natural habitats. Lastly, low proportions of host crops in the landscape were associated with higher abundances of natural enemies. Taken together, our results indicate that crop diversification is not a ‘one size fits all’ strategy to control agricultural pests, and that other landscape characteristics, such as high amounts of semi‐natural habitats, must be considered to enhance biological pest control services.

Factors driving thrips pressure across strawberry-growing regions in Switzerland - Lucien Schneeberger; Angelos Mouratidis; Virginie Dekumbis; Lindsey Norgrove; Louis Sutter (Journal of Pest Science, 2026)
Thrips are important pests of everbearing strawberries worldwide. The emergence of resistance and the ban on several active ingredients mean that alternatives to insecticides need to be developed. Augmentative biological control in many cases has proved successful in controlling thrips; however, in certain cases it fails to keep thrips below the economic damage threshold. Identifying key factors influencing thrips populations is essential. We aimed to assess how thrips population dynamics varied by thrips species, grower practice and location of strawberry plots. In 2022 and 2023, a network of 43 plots in all the main strawberry-growing regions of Switzerland was established. Thrips were counted, adults identified to species level, and the management practices of the growers as well as the crops, topography and temperatures of the plots were recorded. The main species were Frankliniella occidentalis (68% of samples), Thrips tabaci (13%), F. intonsa (12%), and T. fuscipennis (5%) in varying proportions from one plot to another. Only the environmental factors altitude, temperature and distance from a meadow explained a sufficient proportion of thrips population variability. We also observed a link between the distance to the forest and the extent of damage done by thrips to strawberries. No differences were detected between the control strategies used suggesting that the use of insecticides or biocontrol agents is similarly effective. These results underscore the importance of considering the landscape and surrounding host plants in thrips management strategies.

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Pest trap and natural enemy nursery merged in Lobularia maritima? - Janique Koller; Lindsey Norgrove; Virginie Dekumbis; Dylan Maret; Louis Sutter (Arthropod-Plant Interactions, 2024)
Planting crops to push or pull pests from a main crop and floral enhancements to attract natural enemies are emerging as pivotal agroecological strategies to shift away from synthetic pesticides. The brassica, Lobularia maritima, has great potential to act as a floral enhancement as it is attractive to many insects and improves the fitness of and biocontrol services provided by multiple natural enemies. It has been mainly deployed as an insectary plant; few studies have been conducted on its use as a trap plant. We explored the potential of L. maritima as a targeted flower enhancement in sheltered cropping systems through three case studies: (1) as flower strips alongside a cucumber crop, (2) as flower strips alongside a strawberry crop in a replicated on-farm experiment, and (3) as hanging pots under strawberry cultivation gutters. We monitored beneficial and pest insects in flowers and crops and assessed crop damage. Lobularia maritima stands out as an excellent floral enhancement plant due to its ease of cultivation and its ability to flower consistently over an extended period. Generalist predatory bugs, such as Orius laevigatus and Macrolophus pygmaeus , had higher densities on L. maritima than on other flowers grown next to strawberries. We found more thrips on L. maritima and less thrips on crops in two out of three experiments, compared with controls. Further research is needed to confirm if L. maritima is an effective trap crop for thrips and other pests and to detect possible dis-services, such as the attraction of phytophagous bugs.

A parasitoid wasp allied with an entomopathogenic virus to control Tuta absoluta - Janique Koller; Jérémy Gonthier; Lindsey Norgrove; Judit Arnó; Louis Sutter; Jana Collatz (Crop Protection, 2024)

Models for the practitioner: Predicting the efficient biocontrol of Tuta absoluta under different management scenarios - Jérémy Gonthier; Janique Koller; Judit Arnó; Jana Collatz; Louis Sutter (Crop Protection, 2023)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Correction to: Agroforestry can enhance foraging and nesting resources for pollinators with focus on solitary bees at the landscape scale - Sonja Kay; Elisabeth Kühn; Matthias Albrecht; Louis Sutter; Erich Szerencsits; Felix Herzog (Agroforestry Systems, 2021)

The effectiveness of flower strips and hedgerows on pest control, pollination services and crop yield: a quantitative synthesis - Matthias Albrecht; David Kleijn; Neal M. Williams; Matthias Tschumi; Brett R. Blaauw; Riccardo Bommarco; Alistair J. Campbell; Matteo Dainese; Francis A. Drummond; Martin H. Entling; Dominik Ganser; G. Arjen de Groot; et al. (Ecology Letters, 2020)
Floral plantings are promoted to foster ecological intensification of agriculture through provisioning of ecosystem services. However, a comprehensive assessment of the effectiveness of different floral plantings, their characteristics and consequences for crop yield is lacking. Here we quantified the impacts of flower strips and hedgerows on pest control (18 studies) and pollination services (17 studies) in adjacent crops in North America, Europe and New Zealand. Flower strips, but not hedgerows, enhanced pest control services in adjacent fields by 16% on average. However, effects on crop pollination and yield were more variable. Our synthesis identifies several important drivers of variability in effectiveness of plantings: pollination services declined exponentially with distance from plantings, and perennial and older flower strips with higher flowering plant diversity enhanced pollination more effectively. These findings provide promising pathways to optimise floral plantings to more effectively contribute to ecosystem service delivery and ecological intensification of agriculture in the future.

Agroforestry can enhance foraging and nesting resources for pollinators with focus on solitary bees at the landscape scale - Sonja Kay; Elisabeth Kühn; Matthias Albrecht; Louis Sutter; Erich Szerencsits; Felix Herzog (Agroforestry Systems, 2020)

The interplay of landscape composition and configuration: new pathways to manage functional biodiversity and agroecosystem services across Europe - Emily A. Martin; Matteo Dainese; Yann Clough; András Báldi; Riccardo Bommarco; Vesna Gagic; Michael P.D. Garratt; Andrea Holzschuh; David Kleijn; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Simon G. Potts; et al. (Ecology Letters, 2019)
Managing agricultural landscapes to support biodiversity and ecosystem services is a key aim of a sustainable agriculture. However, how the spatial arrangement of crop fields and other habitats in landscapes impacts arthropods and their functions is poorly known. Synthesising data from 49 studies (1515 landscapes) across Europe, we examined effects of landscape composition (% habitats) and configuration (edge density) on arthropods in fields and their margins, pest control, pollination and yields. Configuration effects interacted with the proportions of crop and non‐crop habitats, and species’ dietary, dispersal and overwintering traits led to contrasting responses to landscape variables. Overall, however, in landscapes with high edge density, 70% of pollinator and 44% of natural enemy species reached highest abundances and pollination and pest control improved 1.7‐ and 1.4‐fold respectively. Arable‐dominated landscapes with high edge densities achieved high yields. This suggests that enhancing edge density in European agroecosystems can promote functional biodiversity and yield‐enhancing ecosystem services.

The loss of indirect interactions leads to cascading extinctions of carnivores - Dirk Sanders; Louis Sutter; F. J. Frank van Veen (Ecology Letters, 2013)
Species extinctions are biased towards higher trophic levels, and primary extinctions are often followed by unexpected secondary extinctions. Currently, predictions on the vulnerability of ecological communities to extinction cascades are based on models that focus on bottom‐up effects, which cannot capture the effects of extinctions at higher trophic levels. We show, in experimental insect communities, that harvesting of single carnivorous parasitoid species led to a significant increase in extinction rate of other parasitoid species, separated by four trophic links. Harvesting resulted in the release of prey from top‐down control, leading to increased interspecific competition at the herbivore trophic level. This resulted in increased extinction rates of non‐harvested parasitoid species when their host had become rare relative to other herbivores. The results demonstrate a mechanism for horizontal extinction cascades, and illustrate that altering the relationship between a predator and its prey can cause wide‐ranging ripple effects through ecosystems, including unexpected extinctions.